Analisis Pengembangan Potensi Wisata Edukasi Di Universitas Negeri Padang - Putri, Olga Anissa; Susanti, Retnaningtyas (CV. ITTC INDONESIA, 2024)
This research is motivated by educational tourism which has the potential to generate income for Padang State University. This can be seen from the number of visitors who come to Padang State University. The purpose of this research is to analyze the development of educational tourism potential at Padang State University. This research uses a qualitative approach and descriptive method with data collection techniques through interviews, observation and documentation. Key informants in the research are informants from UNP Public Relations & Protocol, 2 visitors who visit UNP, 2 managers of hotel tour & travel business units and 2 UNP students. These informants can be questions related to opportunities for developing educational tourism at UNP. Data analysis techniques by grouping the data that has been obtained for processing, conducting a SWOT analysis, entering it into a SWOT matrix, and analyzing strategies from the SWOT matrix. The results of the study show an analysis of the development of educational tourism potential at Padang State University, namely by accepting criticism and suggestions from informants regarding the Potential for sustainable value, Potential for awards/certificates, Potential for enriching knowledge, and Potential for adventure.